Efektivitas terapi kelompok Dialectical Behavior Therapy (DBT) dan hipnotis 5 jari terhadap kualitas hidup pasien dengan gangguan stres pasca trauma (PTSD) Di Yayasan Griya Cinta Kasih - LKS Disabilitas Mental Jombang - Sulistiawati; Sholikhah, Siti; Saifudin, Moh. (Jurnal Keperawatan Muhammadiyah, 2025)
Post-Traumatic Stress Disorder (PTSD) is a psychological condition that can negatively impact an individual’s quality of life. Non-pharmacological interventions such as Dialectical Behavior Therapy (DBT) and Five-Finger Hypnosis are increasingly used to help patients manage PTSD symptoms. This study aims to evaluate and compare the effectiveness of DBT and Five-Finger Hypnosis in improving the quality of life of PTSD patients. The study employed a quasi-experimental design with a pre-test and post-test approach in two intervention groups, each consisting of 30 respondents selected through purposive sampling. The instrument used for assessment is WHOQOL-BREF, and data analysis was conducted using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results indicated that both interventions significantly improved the quality of life of PTSD patients (p < 0.05). However, Five-Finger Hypnosis demonstrated greater effectiveness compared to DBT, with a significance value of p = 0.000. Based on these findings, it can be concluded that Five-Finger Hypnosis is more effective in enhancing the quality of life for PTSD patients due to its deep relaxation technique, which significantly reduces anxiety and stress levels. Therefore, Five-Finger Hypnosis should be considered as an effective non-pharmacological alternative therapy for PTSD treatment.